Mainstreaming Climate Risk Management through Ethiopia’s ATVET Agricultural Education System - Hansen, James; Dinku, Tufa; Grossi, Amanda; Belay, Berhanu; Lemma, Esayas; Alemayehu, Fikadu; Degene, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Strengthening the capacity of agricultural extension and advisory services (EAS) to use available climate information services (CIS) to support farmers to better manage climate risks is an important part of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project strategy to enhance agricultural resilience in Africa. Ethiopia’s strong public agricultural extension system offers particularly promising opportunity to scale the impacts of agricultural CIS and build resilience of the country’s agriculture sector. The Climate Risk Management in Agricultural Extension (CRMAE) is a suite of country-adapted curricula, at varying stages of co-development and adoption in six countries (Ethiopia, Senegal, Kenya, Zambia, Ghana, Mali). This brief summarizes a multi-year process of co-developing the CRMAE curriculum in Ethiopia, and formally adapting it for Agricultural Technical and Vocational Education and Training (ATVET) colleges that train future extension agents.